The Factors That Influence the Adoption of E-Learning Among UTHM Students - Kepar, Nirmawi; Nasuredin, Juzaimi (Research in Management of Technology and Business, 2023)
E-learning is the distribution of educational information using electronic media. One sector experiencing a rapid digital change is higher education globally, as COVID effects have disrupted the reality of the new normal. Disruptive educational innovation changes the current educational approaches and modes of learning by providing new options for learning. Also, more students are opting to complete their coursework online because traditional classroom instruction is strict, inflexible, and ineffective from the student’s perspective. Therefore, this study explained the factors (performance expectancy, effort expectancy, social influence, and facilitating conditions) that influence the adoption of e-learning among UTHM students using the unified theory of acceptance and use of technology (UTAUT). A set of questionnaires were distributed to 800 UTHM students using Google Forms via email and social media platforms and managed to obtain 241 responses, equivalent to a 30.13% of response rate. This study found that performance expectancy, effort expectancy, social influence and facilitating conditions have a significant relationship towards the adoption of e-learning. Thus, this study managed to identify the factors that influence the adoption of e-learning among UTHM students. The future researcher could widen the scope of this study to other universities in Malaysia.